Cyanide detection using a highly selective fluorescent and colorimetrical double channel probe incorporating hybrid naphthopyran–benzothiazole in an aqueous solution. Issue 8 (3rd August 2021) - Li, Qiao; Chang, Jing; Shi, Haixiong; Niu, Teng; Dong, Hongru; Mu, Hongmei
ABSTRACT: A highly selective red-emitting fluorescent and colorimetric double-channel probe incorporating a conjugated benzopyran–benzothiazole system is proposed for the detection of cyanide (CN − ) in water samples. Under the presence of CN −, the probe displays red fluorescence disappearance, having an immediate (<30 s) visible colour variation from red to colourless. Due to a blocking process where an intramolecular charge transfer occurs, the benzothiazole C = N bond of the probe is attacked by the CN − nucleophile; 1 H NMR titration and DFT calculations for this occurrence varied. Results from this investigation enable feasible and simple test strips to be produced for detecting CN − in water samples. Graphical Abstract: uf0001